Melayani dengan Kerendahan Hati: Spiritualitas Pelayan(an) Guru Sekolah Minggu (Pengasuh) GPM - Sopacuaperu, Eklepinus Jefry; Talupun, Johanna Silvana; Nanuru, Ricardo Freedom (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
This article aims to construct 'the spirituality of service' for the servants, more specifically in regards to the service to children through Sunday school. Therefore, this writing will talk about the meaning of serving with heart. The principles of serving with heart are to be the foundation of the spirituality of service itself. It is a great hope that through the effort of building a spirituality of service that there will be a change of perspective towards serving, that it is no longer a mere routine or obligation, but more than that is an act of faith, an exercise of spirituality, and an act of spirituality to live out in daily life.